Optical characterization of porous silicon monolayers decorated with hydrogel microspheres - Balderas-Valadez, Ruth F.; Weiler, Markus; Agarwal, Vivechana; Pacholski, Claudia (Nanoscale research letters, 2014)
The optical response of porous silicon (pSi) films, covered with a quasi-hexagonal array of hydrogel microspheres, to immersion in ethanol/water mixtures was investigated. For this study, pSi monolayers were fabricated by electrochemical etching, stabilized by thermal oxidation, and decorated with hydrogel microspheres using spin coating. Reflectance spectra of pSi samples with and without deposited hydrogel microspheres were taken at normal incidence. The employed hydrogel microspheres, composed of poly-N-isopropylacrylamide (polyNIPAM), are stimuli-responsive and change their size as well as their refractive index upon exposure to alcohol/water mixtures. Hence, distinct differences in the interference pattern of bare pSi films and pSi layers covered with polyNIPAM spheres could be observed upon their immersion in the respective solutions using reflective interferometric Fourier transform spectroscopy (RIFTS). Here, the amount of reflected light (fast Fourier transform (FFT) amplitude), which corresponds to the refractive index contrast and light scattering at the pSi film interfaces, showed distinct differences for the two fabricated samples. Whereas the FFT amplitude of the bare porous silicon film followed the changes in the refractive index of the surrounding medium, the FFT amplitude of the pSi/polyNIPAM structure depended on the swelling/shrinking of the attached hydrogel spheres and exhibited a minimum in ethanol-water mixtures with 20 wt% ethanol. At this value, the polyNIPAM microgel is collapsed to its minimum size. In contrast, the effective optical thickness, which reflects the effective refractive index of the porous layer, was not influenced by the attached hydrogel spheres.
Gesehen am 25.08.2020